Judgement Modality In The Editorials Of The Epoch Times Newspaper - Suci Sam; Dahlia D. Moelier; Sudirman Maca (Humaniora: Journal of Linguistics, Literature, and Education, 2021)
The purpose of this study was to determine the type of epistemic modality most frequently used and also to determine the speaker's attitude towards his editorial. The level of editorial confidence in the written editorial can be seen by looking at the use of verb modals which is epistemic modality. The writer assesses modality based on qualitatif method to describe the speaker’s attitude and quantitative to determine the type of modality that is the most often used. The data collection procedure was sourced from newspaper and used 43 editorial texts as the research sample. The results of this study found that the type of epistemic modality most often used was the assumptive type which reached 61,8%. The second is the speculative type with a percentage of 26,4%. The third is deductive type with a percentage of 8,9%. And the fourth is concessive type with a percentage of 2,9%. Apart from that, this study also found that the speaker's attitude was doubtful about his proposition when based only on possible conclusions. The speaker's attitude is confident in his proposition when it is based on a sound conclusion. The speaker's attitude of being confident and believing what is necessity to do is based on the only possible conclusion. And the speaker predicts something to be true when the speaker has evidence that contrasts with the proposition.